A lysosome-targeted near-infrared fluorescent probe for cell imaging of Cu2+. (August 2022) - Chen, Yin; Long, Zhiqing; Wang, Chengcheng; Zhu, Jingjing; Wang, Shasha; Liu, Yan; Wei, Peng; Yi, Tao
Abstract: Cu 2+ in lysosomes are closely related to some diseases such as Menke's syndrome, Wilson's diseases and Alzheimer's diseases. Although many fluorescent probes have been constructed for the detection of Cu 2+ in lysosomes, the poor water solubility and short wavelength emission (λem < 600 nm) limit the application of these probes. To solve this problem, a fluorescent probe DHUCu-1 with near-infrared emission was designed and synthesized in this work. DHUCu-1 could detect Cu 2+ in PBS solution (1% alcohol as co-solvent) with high sensitivity and good selectivity. Moreover, DHUCu-1 could target lysosomes and respond to Cu 2+ in lysosomes. This probe thus can be used as a tool for the exploration of physiological functions of Cu 2+ and the related diseases. Graphical abstract: New turn-on fluorescent probe named DHUCu-1 was developed for the detection of Cu 2+ . DHUCu-1 displayed near-infrared emission and could detect Cu 2+ in PBS solution (1% alcohol as co-solvent) with high sensitivity and selectivity. Moreover, DHUCu-1 could target lysosomes and respond to Cu 2+ in lysosomes. Image 1 Highlights: A fluorescent probe with near-infrared emission was designed and synthesized for detecting Cu 2+ . The probe has good water solubility and shows high sensitivity and good selectivity toward Cu 2+ . The probe could target lysosomes and detect intracellular Cu 2+ in lysosomes.